Assessment of stress in the inclusion of nursing students in hospital practice - Fernandes Pereira, Francisco Gilberto; Nunes Caldini, Luana; Di Ciero Miranda, Maira; Áfio Caetano, Joselany (Investigación y Educación en Enfermería, 2014)
Objective. To verify the presence of stress among undergraduate nursing students in different stages of hospital practice. Method. Descriptive, cross-sectional study addressing 86 nursing students in their 6th, 7th, and 9th semesters in 2011. An instrument developed by Costa and Polak for the Assessment of Stress Among Nursing Students was used. It is composed of six domains: performance of practical activities, professional communication, time management, environment, professional training, and theoretical activity. Results. Most participants were women (95%) and the average age was 23 years old. A total of 84% of students passed the program’s courses and 91% participated in extracurricular activities. Stressors are present during the entire program but intensify when students are introduced to care practice with an emphasis on the domain of professional training; related stress was high in all the semesters. The scores concerning the practical activity domain were higher only in the 6th semester. There were statistically significant levels at 0.01 and 0.10 in the difference in the averages in the domains of training and time management, respectively, between the semesters. As the students advance in the program, scores obtained in the domains presented by AEEE change. As stress can interfere in the performance and learning of nursing students, coping strategies should be devised to enable them to deal with stress during the program. How to cite this article: Pereira FGF, Caldini LN, Miranda MC, Caetano JA. Assessment of stress in the inclusion of nursing students in hospital practice. Invest Educ Enferm. 2014; 32(3): 430-437.